Prevalence of airborne Aspergillus in the air of monuments: Impact on biodeterioration and human health - Megha Agarwal, Kavita Sharma and (Current Botany, 2011)
<span style="font-weight: normal; font-size: 8pt; background: white; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Aspergillus<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> <span style="font-weight: normal; font-size: 8pt; background: white; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">in<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">fections have grown in importance in the last years. The Aspergilli have always been a factor in the human environment. Biodeterioration processes result from complex interactions of surface-invading microbes with each other as well as with the surface material. Fungal ability in production of pigments and organic acids have crucial role in discoloration and degradation of monuments. Air acts as a vehicle for the dispersion of microorganisms. Aspergillus species can cause various forms of disease. This investigation focuses on mycological survey of the Sita Devi Temple of Devarbija, Bhandedwal Temple of Arang Laxman temple of Sirpur and Pateleswar Mahadev Temple of Bilaspur (C.G.), India. Species of Aspergillus reported as a dominant fungal flora followed by Alternaria, Penicillium, Curvularia, Cladosporium, Fusarium, Mucor and Rhizopus from all the sample sites. The purpose of this investigation is to summarize the current knowledge about this important group of fungi.